Co-designing family planning interventions: Insights from religious leaders in urban eastern Uganda - Jacquellyn Nambi Ssanyu; Catherine Birabwa; Kharim Mwebaza Muluya; Felix Kizito; Sarah Namutamba; Moses Kyangwa; Othman Kakaire; Peter Waiswa; Rornald Muhumuza Kananura (Elsevier, 2026)
Background: In Uganda, religion strongly influences family planning (FP) practices, yet religious leaders are often excluded from FP program design and delivery. Engaging them meaningfully could help address misconceptions and improve voluntary FP uptake. Methods: We applied Community-Based Participatory Action Research and Human-Centered Design to engage 16 religious leaders from Muslim, Catholic, Anglican, and Pentecostal faiths in Jinja City and Iganga Municipality, eastern Uganda. Faith-specific discussions were conducted using a structured agenda and co-moderated by participants. Data from audio recordings and notes were transcribed, translated, and analyzed thematically. Results: All religious leaders expressed openness to FP but differed in their definitions and preferred methods. Christian leaders associated FP with responsible parenthood and manageable family sizes, while Muslim leaders emphasized parental responsibility without limiting fertility, stressing faith in divine provision. Natural methods were widely accepted, while hormonal methods were met with caution due to health concerns. There was unanimous opposition to providing FP to unmarried adolescents, with abstinence endorsed as the only acceptable option. Leaders welcomed the opportunity to share FP messages through their platforms, provided materials were accurate, respectful of religious values, and comprehensive in scope. Conclusions: Religious leaders can play a pivotal role in advancing FP awareness and acceptance when engaged as partners in design and messaging. Programs should prioritize culturally sensitive communication, clarify misconceptions, and co-create strategies that align with faith-based perspectives. These approaches can enhance trust, shift social norms, and improve access to FP services, especially in communities where religious influence is strong.
Keywords: Family planning; Religious leaders; Community-based participatory research; Co-design; Uganda